Management compensation, monitoring and aggressive corporate tax planning - Melanie Steinhoff (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2015)
The empirical literature shows that management incentives often reduce corporate tax aggressiveness. Focussing on the riskiness of tax aggressiveness this paper offers one explanation for the observed negative relation. Using an agency framework, I analyze the manager's choice of effort dedication in other tasks and her explicit choice of the firm's tax risk. I show that corporate tax aggressiveness may decrease with compensation incentives. By choosing the tax risk, the manager (partly) determines her compensation risk. When the manager is assumed to be risk averse, an increase in compensation incentives motivates her to reduce her compensation risk through a less aggressive tax planning strategy. Further, a good governance structure may mitigate this effect of incentive compensation when marginal returns for tax planning are sufficiently ciently low. I also demonstrate that the tax deductibility of performance-based pay yields less aggressive tax planning.
Keywords: H25; D82; D21; 330; management incentives; hidden action; corporate tax planning